Sex-specific regulation of weight and puberty by the Lin28/let-7 axis. Issue 3 (23rd December 2015) - Corre, Christina; Shinoda, Gen; Zhu, Hao; Cousminer, Diana L; Crossman, Christine; Bellissimo, Christian; Goldenberg, Anna; Daley, George Q; Palmert, Mark R
Abstract : Growth and pubertal timing differ in boys and girls. Variants in/near LIN28B associate with age at menarche (AAM) in genome-wide association studies and some AAM-related variants associate with growth in a sex-specific manner. Sex-specific growth patterns in response to Lin28b perturbation have been detected in mice, and overexpression of Lin28a has been shown to alter pubertal timing in female mice. To investigate further how Lin28a and Lin28b affect growth and puberty in both males and females, we evaluated Lin28b loss-of-function (LOF) mice and Lin28a gain-of-function (GOF) mice. Because both Lin28a and Lin28b can act via the conserved microRNA let-7, we also examined let-7 GOF mice. As reported previously, Lin28b LOF led to lighter body weights only in male mice while Lin28a GOF yielded heavier mice of both sexes. Let-7 GOF mice weighed less than controls, and males were more affected than females. Timing of puberty was assessed by vaginal opening (VO) and preputial separation (PS). Male Lin28b LOF and male let-7 GOF, but not female, mice displayed alteration of pubertal timing, with later PS than controls. In contrast, both male and female Lin28a GOF mice displayed late onset of puberty. Together, these data point toward a complex system of regulation by Lin28a, Lin28b, and let-7, in which Lin28b and let-7 can impact both puberty and growth in a sex-specific manner, raising the possibility that this pathway may contribute to differential regulation of male and female growth and puberty in humans.